Review of ecosystem flow regulating functions in the Zambezi Basin. Project report submitted to UNEP under the SADC project "Dam Synchronization and Flood Releases in the Zambezi River Basin". - McCartney, Matthew P.; Xueliang Cai; Smakhtin, Vladimir U. (International Water Management Institute, 2011)
Water infrastructure is a cornerstone of economic development. In the Zambezi River Basin huge investments have been made in dams for hydropower, irrigation, water supply and flood control. Ecosystem functions are central to outcomes from dams. Not only does the performance of dams depend on ecosystem functions but dams also modify them (e.g. by changing natural flow regimes). It is by changing ecosystem functions (and hence ecosystem services) that dams often have their greatest impact on the livelihoods of poor people. However, investment decisions and, subsequently the management of dams, rarely consider ecosystem functions. Trade-offs and synergies between dams and ecosystem functions often go unrecognized and, as a result, the benefits accruing from dams are typically sub-optimal. One reason for the failure to consider ecosystem functions is lack of understanding of them and how they translate into services for people. It is not clear which ecosystems perform which functions or how they will be affected by a dam. For example, whilst it is widely understood that in relation to hydrology, different ecosystems provide different regulating functions, there is little quantitative information on the extent to which they do this or the dynamic nature of such functions. If ecosystem functions, and specifically flow regulating functions, are to be considered in dam planning and management more information and a method to incorporate them into decision-making processes is required. Based on a literature review this report summarizes i) evidence of the flow regulating functions of the major ecosystems in the Zambezi basin and ii) methods for evaluating ecosystem flow regulating functions. Finally, it proposes an approach for developing a method that could contribute to a decision support system for the synchronization of dam operation in the basin.